Analisis Tingkat Kedisiplinan Mahasiswa dalam Kegiatan Pembelajaran - Sofyan Abdi; Fikri Nurfadillah; Khofifah Az; Nadia Nadra Kamila; Salma Hulwa Akifah; Yulia Setya Ningrum; Nurtika Sahar Nabila; Aryadita Utami Putri; Anastasya Budiarsy (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Discipline is something related to someone's control of various forms of regulation. The purpose of this research is to direct students so that they learn about good things as a preparation for the future, when they are very dependent on self-discipline. This study uses a descriptive method with a quantitative approach. With a large number of samples ± there are 51 UHAMKA students in the teaching and education faculties of the 2019/2020 academic year. The research instrument used a questionnaire or questionnaire and library literature in the form of journals and books. And this validity approach is tested using construct validity and for this reliability approach using internal consistent reliability testing. The procedure for taking this sample was carried out by systematic random sampling. And the data collection was used by distributing questionnaires which were distributed via Google Formular to students analyzing data for variable and reliable testing using IBM SPSS 26. And using a one-sample t-test statistic. The results showed that: there were 33 students (78%) who had a very high level of discipline. There are 16 students (56-77%) who have a moderate level of discipline. There are 2 students (55%) who have a low level of discipline. Based on the explanation above, it can be said that the level of student discipline is included in the high category. This result is the possibility that students choose good answers or indeed good discipline. Based on the data above, the high level of student discipline shows that students at FKIP Uhamka have good obedience, obedience, and order. This is in line with Susanto's statement (2018) that discipline is influenced by factors including: students following and obeying applicable regulations, self-awareness, educational tools, punishment, exemplary attitude, disciplinary environment, and disciplinary training. However, there are still students who adhere to a low level of discipline (55%). This can be spread by the background of the students themselves who are less disciplined about the rules applied by the university and because there is no awareness about the importance discipline.